2020
DOI: 10.1177/1468087420929768
|View full text |Cite
|
Sign up to set email alerts
|

On the application of artificial neural networks for the prediction of NOx emissions from a high-speed direct injection diesel engine

Abstract: This article considers the application and refinement of artificial neural network methods for the prediction of NO x emissions from a high-speed direct injection diesel engine over a wide range of engine operating conditions. The relative computational cost and performance of two backpropagation algorithms, Levenberg–Marquardt and Bayesian regularization, for this application are compared, with the Levenberg–Marquardt algorithm demonstrating a significant cost advantage. This work also assesses the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…25 The detailed process of feature selection is highlighted in our previous study. 19 The results suggest 14 input features in the dataset are needed for the construction of an ANN NO x model. A brief discussion of each parameter chosen is included in this article.…”
Section: Operating Conditions Including Those Excluded From the Training Dataset (Validation Data)mentioning
confidence: 99%
See 2 more Smart Citations
“…25 The detailed process of feature selection is highlighted in our previous study. 19 The results suggest 14 input features in the dataset are needed for the construction of an ANN NO x model. A brief discussion of each parameter chosen is included in this article.…”
Section: Operating Conditions Including Those Excluded From the Training Dataset (Validation Data)mentioning
confidence: 99%
“…However, a systematic overprediction of CoV was observed for low CoVs while higher CoVs were underpredicted by the ANN model suggesting missing physical parameters for the ANN input features. More recently Fang et al 19 In this study, we explore the applicability of the ANN method for the prediction of NO x emissions of a high-speed direct injection diesel engine undergoing transient load steps. The model is built from a substantial experimental dataset, which includes 7 months of engine testing (1108 individual experiments) from the University of Oxford single-cylinder diesel research engine running under various steady-state conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimisation results were then validated against test bench data. Fang et al 27 used filtering techniques to identify significant parameters in combination with neural networks to predict the nitrous oxide emissions of a diesel engine. Further, specialised approaches of modelling include the prediction of the cylinder peak pressure using a high frequency crank angle measurement in Dunne and Bennett 28 or a two stage calibration approach for a two step chemical reaction mechanism by Men et al 29 A comprehensive literature study on the model-based diesel engine calibration has been conducted by Nikzadfar and Shamekhi.…”
Section: The State Of the Artmentioning
confidence: 99%
“…The study focused on identifying the most important engine parameters for accurate NO x prediction over a wide range of operation. This study highlighted 14 parameters that have the biggest effect on NO x , based on a Pearson correlation analysis, and shown that ANN models are capable of accurately predicting NO x emissions even when tested outside the training range of the model [24] Despite their powerful generalisation abilities, like other empirical models, their performance deteriorates when deployed outside their training range. By using the widest limits of the data during training provides the best chance of extrapolating for an ANN model.…”
Section: Introductionmentioning
confidence: 99%